A descriptive study investigating functional balance in deaf school-aged children: towards the adaptation and validation of subjective questionnaires - Mbhele, Sphilile (Department of Health and Rehabilitation Sciences, 2026)
BACKGROUND: Balance deficits are common in children with deafness. They have an impact on the child's general well-being and holistic development. However, the extent to which children with deafness experience this condition is relatively unknown given the inability of children to communicate their symptoms to healthcare professionals and the lack of self-assessment tools for this population. Although balance function has been studied in literature, the functional impact of balance deficits in children with deafness remains undervalued and under-researched. OBJECTIVE: To evaluate functional balance by quantifying symptoms of imbalance, balance-related handicap and measuring balance performance in school-aged children with deafness and children with normal hearing between the ages of 9 to 17 years. METHODS: A descriptive, case-controlled research study was conducted with 155 children; 97 with deafness and 58 with normal hearing of both sexes, between the ages of 9–17 years (mean age 14 years). The PVSQ was used to quantify balance symptoms, DHI-CA to quantify dizziness-related handicap, and the EQ-5D-Y proxy version questionnaire to determine health- related quality of life. Physical outcome measures included visual acuity, the Mini-Balance Evaluation Systems Test (Mini-BESTest) and the Modified Clinical Test of Sensory Interaction in Balance (m-CTSIB). RESULTS: The PVSQ showed a high internal consistency (Cronbach's α=0.904) and construct validity demonstrated good sensitivity (80%) and specificity (90%). The DHI-CA showed similar results with internal consistency of Cronbach's α=0.949, and sensitivity and specificity of 80%. Significant differences (p=<. 001) were noted between the two groups. Children with deafness showed reduced balance scores on the Mini-BESTest and m-CTSIB (p=<0.001), and had reduced dynamic and static visual acuity when compared with children with normal hearing. A significant relationship was noted between the balance tests and the PVSQ and DHI-CA. The EQ-5D-Y proxy version questionnaire indicated that children with deafness experienced difficulties in all five domains, while children with normal hearing showed difficulties in only two domains (Having pain or discomfort and Feeling worried, sad or unhappy). A correlation was found between the PVSQ, DHI-CA and domain 4 (Doing usual activities) and domain 5 (Having pain and discomfort) of the EQ-5D-Y proxy version questionnaire. CONCLUSION: Children with deafness presented with greater balance difficulties than normal hearing children of the same age group. The adapted PVSQ is able to detect symptoms of imbalance, while the adapted DHI-CA can describe the severity of the handicap imposed by balance symptoms in children with deafness. These tools were able to discriminate between children with impairment versus those from the control sample. Thus, the tools adapted in this study are suitable for identifying balance symptoms and the related impact thereof. These tools will provide invaluable information to healthcare professionals about a child's self-reported balance outcomes, and assist in the subsequent individualisation of therapeutic interventions, ultimately playing a significant role in enhancing the quality of life of children with deafness.